Ecto-nucleotidase pathway is altered by different treatments with fluoxetine and nortriptyline. - Eduardo Luiz Pedrazza (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-09-06T12:05:27Z No. of bitstreams: 2 Ectonucleotidase_pathway_is_altered_by_different_treatments_with_fluoxetine_and_nortriptyline.pdf: 626955 bytes, checksum: 8cefa4e3f3c0f027b30a7c7039d9da81 (MD5) Ectonucleotidase_pathway_is_altered_by_different_treatments_with_fluoxetine_and_nortriptyline.pdf: 626955 bytes, checksum: 8cefa4e3f3c0f027b30a7c7039d9da81 (MD5)